Analisis Vegetasi Gulma Berdaun Lebar pada Lahan Budidaya Tanaman Jagung (Zea mays L.) di Dataran Tinggi dan Dataran Rendah - Humaira, Farha Niswa Al; Rahmawanti, Fitrianti; Maharani, Zerlinda Aqila Gitta; Jannah, Ananda Rohmatul; Kamaluddin, Muhammad; Tarigan, Puji Lestari (Politeknik Negeri Lampung, 2025)
Corn plants are considered as one of the staple crops in Indonesia. Corn is an important crop after rice as a source of carbohydrates, and corn has high strategic and economic value. In producing corn plants, their growth is very much determined by how they are managed. Several factors that greatly affect the decline in corn growth are the presence of weeds growing in cultivated land. The presence of these weeds can disrupt plants. In addition, weeds become competing plants for cultivated plants to get water, light and nutrients. The method used in conducting this weed diversity analysis is the quadratic method. The method used is to identify weeds found in corn plants in the highlands of Malang Regency and the lowlands of Siduarjo Regency. The results obtained from observations of weed vegetation in the highlands found 9 families, 12 species and 152 individuals, while in the lowlands found 2 families, 2 species and 173 individuals. The Ageratum conyzoides species in the highlands has the highest relative density, which is 48.05%, while in the lowlands, the Amaranthus viridis species has a relative density of 89.60%.